Periodontal pathogens in atheromatous plaque - Saroj K. Rath; Manish Mukherjee; R Kaushik; Sourav Sen; Mukesh Kumar (Wolters Kluwer Medknow Publications, 2014)
Background: There has been increasing attention paid in recent years to the possibility that oral bacterial infection, particularly periodontal disease may influence the initiation and or progression of systemic diseases. These studies confirm the observation that heart disease is the most commonly found systemic condition in patients with periodontal disease. Moreover, the literature has also highlighted substantial evidence indicating the presence of Gram-negative periodontal pathogens in atheromatous plaques. Aim: This study intends to investigate the possible association between periodontal health and coronary artery disease by evaluating periodontal status, association between the periodontal plaque and coronary atheromatous plaques for presence of micro-organisms such as, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, and Tannerella forsythia. Materials and methods: A case-control study was designed with seven patients who had undergone coronary endarterectomy for cardiovascular disease and 28 controls. The periodontal examination for cases was performed 1 day before vascular surgery and the controls were clinically examined. The atheromatous plaque sample collected during endarterectomy and the intraoral plaque samples were subjected to polymerase chain reaction for identification of A. actinomycetemcomitans, P. gingivalis, P. intermedia and T. forsythia. Results: The presence of periodontal bacteria DNA in coronary atheromatous plaques and sub-gingival plaque samples of the same patients was confirmed by this study. CONCLUSION A correlation was established between putative bacteria contributing to atheromatous plaques and species associated with periodontal disease. One particularly important study to be carried out is the investigation of a possible clinically meaningful reduction in coronary heart disease resulting from the prevention or treatment of periodontal disease.